Wet season upwelling and dry season chlorophyll-a describe interannual growth rates of porites in Southern China - Yang, Teng Teng (2014)
Southern China hosts coral communities in marginal environments that are characterized by low linear extension rates, low coral cover and/or no reef formation, thus providing natural laboratories to study coral communities with below average growth rates. Here we compare the annual linear extension rates over 10 years (range 1.2 to 11.4 mm yr−1) of six Porites sp. coral cores collected from Hong Kong with monthly hydrographic data from the Hong Kong Environmental Protection Department. At all sites, low-density, dry season extension were more variable than high-density, wet season extension and on average, was lower at two of the three sites. We applied multi-variate linear regressions that revealed high-density, wet season band extension to inversely correlate most significantly to temperature (r = −0.39, p<0.01). In contrast, low-density, dry season band extension was more variable and correlated most significantly with dry season chlorophyll-a (Chl-a) (r = 0.64, p<0.001). Additionally, we find that corals at the site with highest dry season Chl-a have the highest dry season extension lengths. Our findings indicate that relative mixing of fresh and salt water in the wet season and primary productivity in the dry season, and their influences on aragonite saturation, are likely to impact interannual coral extension variability in marginal environments.